ANALISIS RASIO KEUANGAN TERHADAP KINERJA PERUSAHAAN PT BANK RAKYAT INDONESIA PERSERO TBK - Dita Fitrianingsih; Vivi Adeyani Tandean (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the financial performance of PT BRI over the period 2019–2023 using five key financial ratios: the Current Ratio, BOPO (Operating Expenses to Operating Income), Profit Margin, Return on Equity (ROE), and Debt to Asset Ratio (DAR). The method employed is descriptive quantitative, using secondary data obtained from PT BRI 's annual financial statements over the five-year period. The results show that the Current Ratio ranges between 1.33 and 1.38 times, below the industry standard of 2 times, indicating poor liquidity. BOPO decreased from 53.61% in 2022 to 49.98% in 2023, suggesting operational efficiency that needs to be evaluated as it falls outside the industry standard range of 50%–75%. The Profit Margin increased from 19.18% in 2020 to 39.33% in 2023, exceeding the industry standard of 20%, indicating improved profitability. ROE rose from 8.13% in 2020 to 19.09% in 2023, but it remains below the industry standard of 40%. Meanwhile, DAR remains high, ranging from 83.73% to 83.89%, well above the industry standard of 35%, indicating a high dependency on debt.